Review Lean Manufacturing Model of Production Management under the Preventive Maintenance Approach to Improve Efficiency in Plastics Industry SMES: A Case Study - Flores, Juan Carlos Quiroz; Vega-Alvites, Melanie Lucia (South African Journal of Industrial Engineering, 2022)
Failure to deliver orders because of low production capacity is one of the main problems faced by companies in the plastics sector. This has repercussions, creating customer dissatisfaction and directly affecting profits by increasing production costs. Among the main causes of these problems is production downtime, which is caused by high set-up times and machine failures during the production process. To solve these problems, a lean manufacturing model is proposed that includes 5S, SMED (Single Minute Exchange of Die), TPM (Total Productive Maintenance), and Jidoka tools. This model was validated in a company dedicated to the production of plastics by injection moulding, which resulted in an increase in OEE (Overall Equipment Effectiveness) of 13 per cent and a reduction in set-up times of 48 per cent.